Macrophytes in tropical shallow lakes: An important food item to benthic entomofauna or an underused resource?. Issue 2 (11th April 2019) - Shimabukuro, Erika M.; Henry, Raoul
Abstract: Although macrophytes are known to increase benthic diversity in lakes, the importance of this resource as food for the insects living at the bottom of these ecosystems are still poorly understood. This study assessed the diets of benthic Chironomidae and Campsurus (Ephemeroptera) in two environments: a lake with macrophytes (M+) and another without macrophytes (M−). We expected a differential use of food resources in M+, where plant tissue is particularly important for the aquatic insects' diet. The diet of 734 individuals from 16 taxa were analyzed. Contrary to expectations, benthic insects consumed low amounts of plant tissue. This finding led us to investigate whether the presence of macrophytes in lakes would indirectly contribute to the benthic insects' feeding, as more food resources were explored in M+ and a spatial variation of resources intake was observed in this lake, in contrast to the homogeneous feeding in M−. We highlight that macrophytes were responsible for the organic matter build‐up in the sediment, especially at the lake region dominated by these plants, and contributed to increase the deposition of high‐quality amorphous organic matter, which favored taxa in M+ that fed exclusively on this item. The lower diversity of food items exploited in M−, and the Tanypus alga‐based diet in this lake, indicates the low quality of organic resources in its sediment. Although macrophytes were indirectly beneficial for benthic insects' feeding, we found that this is not an attractive resource for prompt ingestion by most benthic taxa. Abstract : Although macrophytes are known to increase benthic diversity in lakes, the importance of this resource as food for the insects living at the bottom of these ecosystems is still poorly understood. This study assessed the diets of benthic Chironomidae and Campsurus (Ephemeroptera) in two environments: a lake with macrophytes, and another without macrophytes. We observed a differential use of food resources between lakes, but contrary to our expectations macrophytes are not an attractive resource for prompt ingestion by most benthic taxa.